Pathogenic signature of invasive non-typhoidal Salmonella in Africa: implications for vaccine development - Giulia Piccini; Emanuele Montomoli (Taylor & Francis Group, 2020)
Invasive non-typhoidal Salmonella (iNTS) infections are a leading cause of bacteremia in Sub-Saharan Africa (sSA), thereby representing a major public health threat. Salmonella Typhimurium clade ST313 and Salmonella Enteriditis lineages associated with Western and Central/Eastern Africa are among the iNTS serovars which are of the greatest concern due to their case-fatality rate, especially in children and in the immunocompromised population. Identification of pathogen-associated features and host susceptibility factors that increase the risk for invasive non-typhoidal salmonellosis would be instrumental for the design of targeted prevention strategies, which are urgently needed given the increasing spread of multidrug-resistant iNTS in Africa. This review summarizes current knowledge of bacterial traits and host immune responses associated with iNTS infections in sSA, then discusses how this knowledge can guide vaccine development while providing a summary of vaccine candidates in preclinical and early clinical development.